Fermented but Not Irradiated Cottonseed Meal Has the Potential to Partially Substitute Soybean Meal in Broiler Chickens - Amin Ashayerizadeh; Vahid Jazi; Fatemeh Sharifi; Majid Toghyani; Hossein Mohebodini; In Ho Kim; Eugeni Roura (Animals, 2024)
This study was conducted to investigate and compare the effects of substituting soybean meal (SBM) with untreated cottonseed meal (CSM), fermented CSM (FCSM), or electron beam-irradiated CSM (ICSM) on the growth performance, cecal microbiota, digestive enzyme activity, apparent ileal digestibility (AID), and excreta gas emission of broiler chickens. A total of 384 one-day-old male broiler chickens were randomly assigned to four experimental diets, with eight replicates per diet and 12 birds per replicate, for six weeks. The experimental diets consisted of a control diet based on corn–SBM and three other diets in which 50% of the SBM (control) was substituted with CSM in its raw, irradiated, and fermented forms. The results showed that throughout the entire rearing period, feeding broiler chickens with ICSM significantly increased average daily gain (ADG) and body weight (BW) compared to the CSM diet (p < 0.05). Replacing 50% of SBM with FCSM led to a significant improvement in BW, ADG, and feed conversion ratio (FCR) compared to the CSM and ICSM diets (p < 0.05). Interestingly, no significant differences in BW, ADG, or FCR were observed between birds fed FCSM and those on the control diet (p > 0.05). Birds fed FCSM diets exhibited the lowest pH value in the crop, ileum, and ceca. Substituting SBM with FCSM significantly reduced Escherichia coli and Clostridium spp. counts in the ceca, while enhancing the presence of Lactobacillus spp. (p < 0.05). The AID of protein and ether extract was higher in the FCSM group than in the CSM and ICSM groups (p < 0.05). Compared to the CSM diet, ICSM feeding improved protein digestibility (p < 0.05). Broiler chickens on the FCSM diet exhibited higher intestinal amylase and protease activity than those on the other diets (p < 0.05). Furthermore, feeding diets containing FCSM significantly reduced ammonia emissions compared to the other diets (p < 0.05). Overall, our results indicated that microbial fermentation of CSM is a more effective approach than irradiation for enhancing the nutritional value of CSM. Therefore, FCSM is recommended as a viable alternative protein source that can safely replace up to 50% of SBM in broiler chicken diets, particularly during times of fluctuating SBM prices and availability issues.